Impact of NPK fertilization on upland rice yield, Nicaragua - Siles, Pablo; Tellez, Orlando; Peng, Yuan-Ching; Zeledón, Yasser (International Center for Tropical Agriculture, 2020)
This dataset contains information of experiments carried out upland rice in two regions of Nicaragua (Caribbean and Pacific Region), as well as a compilation of soils data from different regions in Nicaragua collected during 2019 in seed banks of rice and beans. The experiments were designed to explore the effects of N, P and K in the yield of upland rice. The experiments were carried out on farmer’s field during the 2019 production cycle, the dataset contains yield and aerial biomass of the experiments.